Gels in Medicine and Surgery: Current Trends and Future Perspectives - Luca Fiorillo; Giovanni Luca Romano (Gels, 2020)
Gel is a two-phase elastic colloidal material, consisting of a dispersed liquid incorporated in the solid phase [...]